2007
DOI: 10.1029/2006jd007912
|View full text |Cite
|
Sign up to set email alerts
|

Surface and lightning sources of nitrogen oxides over the United States: Magnitudes, chemical evolution, and outflow

Abstract: [1] We use observations from two aircraft during the ICARTT campaign over the eastern United States and North Atlantic during summer 2004, interpreted with a global 3-D model of tropospheric chemistry (GEOS-Chem) to test current understanding of regional sources, chemical evolution, and export of NO x . The boundary layer NO x data provide top-down verification of a 50% decrease in power plant and industry NO x emissions over the eastern United States between 1999 and 2004. Observed NO x concentrations at 8-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
437
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(480 citation statements)
references
References 72 publications
(127 reference statements)
40
437
3
Order By: Relevance
“…[13] Several previous studies have used GEOS-Chem to interpret in situ measurements of reactive nitrogen Wang et al, 2004;Hudman et al, 2004Hudman et al, , 2007Martin et al, 2006] as well as observations of tropospheric NO 2 columns from satellite instruments [Martin et al, 2003a[Martin et al, , 2004bJaeglé et al, 2005;Guerova et al, 2006;Sauvage et al, 2007;Wang et al, 2007bWang et al, , 2007aBoersma et al, 2008aBoersma et al, , 2008bBucsela et al, 2008]. GEOS-Chem simulations generally agree to within 30% of measured NO x , HNO 3 , and PAN over eastern North America Hudman et al, 2007;Singh et al, 2007] [15] Figure 1 shows seasonal mean tropospheric NO 2 columns from OMI and GEOS-Chem.…”
Section: Simulation Of No 2 From Geos-chemmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] Several previous studies have used GEOS-Chem to interpret in situ measurements of reactive nitrogen Wang et al, 2004;Hudman et al, 2004Hudman et al, , 2007Martin et al, 2006] as well as observations of tropospheric NO 2 columns from satellite instruments [Martin et al, 2003a[Martin et al, , 2004bJaeglé et al, 2005;Guerova et al, 2006;Sauvage et al, 2007;Wang et al, 2007bWang et al, , 2007aBoersma et al, 2008aBoersma et al, , 2008bBucsela et al, 2008]. GEOS-Chem simulations generally agree to within 30% of measured NO x , HNO 3 , and PAN over eastern North America Hudman et al, 2007;Singh et al, 2007] [15] Figure 1 shows seasonal mean tropospheric NO 2 columns from OMI and GEOS-Chem.…”
Section: Simulation Of No 2 From Geos-chemmentioning
confidence: 99%
“…GEOS-Chem simulations generally agree to within 30% of measured NO x , HNO 3 , and PAN over eastern North America Hudman et al, 2007;Singh et al, 2007] [15] Figure 1 shows seasonal mean tropospheric NO 2 columns from OMI and GEOS-Chem. The high-resolution data in Figure 1 (first row) reveal relatively high values in many urban areas such as Los Angeles, San Francisco, Phoenix, Denver, Houston, Dallas, Chicago, Toronto, and the northeast U.S. corridor.…”
Section: Simulation Of No 2 From Geos-chemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Park et al [2007] found strong biomass burning activity throughout the Southeast and GEOS-Chem does not take into account the diurnal cycle of fires (see next section). In summary, all these NO x sources have a strong afternoon maximum and either their source strength (soils, lightning [Hudman et al, 2007]) or their diurnal cycle (power plants, biomass burning) is underestimated. The observed 1000 -1330 LT ratios <1.0 over the southeastern U.S. appear consistent throughout the summer as we also found them for July 2006 (not shown), while we did not find them for the nonsummer month of October 2004 (not shown).…”
Section: Diurnal Variation In No 2 Columns Over Fossil Fuel Source Rementioning
confidence: 99%
“…The model includes a detailed description of tropospheric O 3 -NO x -hydrocarbon chemistry. The model has been used in a range of studies, including the analysis of the impact of background O 3 on surface O 3 over North America [e.g., Fiore et al, 2002] and interpretation of in situ aircraft observations from the International Consortium on Atmospheric Transport and Transformation (ICARTT) aircraft campaign over North America [e.g.. Hudman et al, 2007]. We use version v7-02-04 of GEOS-Chem with a horizontal resolution of 2°Â 2.5°and 55 levels in the vertical from the surface to 0.01 hPa, with 5 levels in the PBL.…”
Section: Geos-chem Modelmentioning
confidence: 99%